THE EFFECTIVENESS OF ARCHIEVEMENTS IN IMPROVING ADMINISTRATIVE SERVICES IN THE GOVERNMENT SECTION IN THE OFFICE OF THE REGENT OF THE REGENCY OF BATU BARA - Sumiati Sumiati; Siti Mardiana; Rudi Salam Sinaga (Universitas Negeri Medan, 2021)
Organizing archives needs to be done with good management. However, the Governance Section of the Batu Bara Regency Regent's Office still has weaknesses, especially in terms of archive management work procedures. The purpose of this study was to find out how the effectiveness of the archives in improving the administrative services of the Governance Section at the Regent's Office of Batubara Regency. and what are the factors that hinder archives in improving the administrative services of the Governance Section at the Batubara Regency Regent's Office? This study uses a descriptive method with qualitative analysis techniques. Data collection techniques with observation, interviews and documentation. The results of this study found job satisfaction has not been effective because employees have not participated in education and training evenly.